Linking Sediment and Water Column Phosphorus Dynamics to Oxygen, Temperature, and Aeration in Shallow Eutrophic Lakes - A. P. Kirol; A. M. Morales‐Williams; D. C. Braun; C. L. Marti; O. E. Pierson; K. J. Wagner; A. W. Schroth (Water Resources Research)
Abstract Water quality improvements in shallow eutrophic lakes are commonly delayed due to loading from legacy phosphorus (P)‐enriched sediments, even with reduced external nutrient loads. It is critical to understand the drivers of internal P loading to suppress or remove this source of P and meet water quality goals. We contrast the drivers of internal P loading in two shallow eutrophic systems (Lake Carmi and Missisquoi Bay). Legacy P dynamics in the unmanipulated systems were compared to Lake Carmi during aeration. In‐situ high frequency water column monitoring along with water and sediment sampling was used to study P dynamics in response to changing lake conditions and aeration. Despite both systems exhibiting P mobility controlled by iron redox cycling, we observed distinct differences in the spatial extent and drivers of internal P loading. Legacy P loading was controlled by seasonal drivers in Lake Carmi, but by spatially variable and highly transient wind driven forcing of hydrodynamics in Missisquoi Bay. Aeration altered the mixing regime of Lake Carmi and shifted loading dynamics to frequent wind‐driven pulses of legacy P to surface waters akin to those of Missisquoi Bay. Mean hypolimnetic dissolved oxygen increased with aeration, but greater oxygen demand rates and periods of anoxia under transient stratification still resulted in internal P loading. Surface P concentrations were higher in summer months with aeration compared to previous years. This research illustrates the dynamic nature of legacy P behavior within and between shallow eutrophic lakes and the challenges in addressing this common water resources threat.